Host response to black sigatoka in Musa germplasm of different ages under natural inoculation conditions - Mobambo, K.N.; Pasberg-Gauhl, C.; Gauhl, F.; Zuofa, K. (Elsevier, 1997)
The development of an early evaluation method for host response of different Musa clones to black sigatoka was investigated under natural inoculation conditions in southeastern Nigeria. Two months old tissue-culture-derived plants of three plantain hybrids and parents of the hybrids were exposed to the natural inoculum of Mycosphaerella fijiensis in a field planted with a susceptible plantain cultivar. The response to M. fijiensis was evaluated on these young plants and on the same clones of mature, field-established plants. Young plants expressed similar resistance responses as mature plants and allowed an earlier evaluation of host-plant response to M. fijiensis. The male diploid banana parent, ‘Calcutta 4', was highly resistant to black sigatoka. The three hybrids displayed partial resistance before flowering while the female parent, a triploid plantain, was susceptible. Disease responses of both mature and young plants ranked in the same order and were highly correlated (P = 0.01). Young-plant response to black sigatoka in Musa germplasm was shown to be a reliable indicator of mature-plant response and a quick means of disease reaction assessment. This could accelerate progress made by breeding programs when producing new black sigatoka-resistant germplasm.